Why Special Education Is Always In Our Hearts? - et. al., Hifzan Binti Mat Hussin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Being part of special education, has successfully shaped a teacher to be more patient, caring and motivated. Many of the special education teachers expressed their willingness to serve longer in special education. They are also willing to sacrifice time, energy and money to build a balanced and independent generation of special needs students. Special education also makes a teacher always resilient in the face of any challenge. Pupils involved with special education have also always been an aspiration to teachers. with the success achieved by the country's athletes with disabilities in world-class sports, has opened the eyes of many to the importance of special education. A brief qualitative study involving this questionnaire was conducted to survey teachers' views on their love of special education. The findings show that, factors such as the value of love for MBK, changes in the special education system, unique and entertaining MBK, good relationship with MBK and support from various parties have been the cause of their love. This study has good implications in helping teachers to remain consistent in providing the best service to special education.